Preparation and photocatalytic performance of micro/nano structured β2-SiW11Mn doped polyaniline. Issue 20 (29th September 2020) - Zhang, Cheng-Li; Ma, Rong-Hua; Liu, Chun-Tao; Yang, Ming-Rui; Wen, Qi; Cao, Rui
Abstract: Micro/nano-structural polyaniline materials were prepared by using thin glass tubes as template in the presence of β2 -SiW11 Mn and ammonium persulfate, which were used as dopant and oxidant, respectively, in this system. The materials were characterized by IR, UV-Vis, XRD, TG-DTA and SEM techniques. The photocatalytic performance of polyaniline, β2 -SiW11 Mn and β2 -SiW11 Mn/PANI composite obtained was investigated using photodegradation of crystal violet as model reaction. The results showed that the photocatalytic activity of β2 -SiW11 Mn/PANI composite was much higher than polyaniline and β2 -SiW11 Mn due to a synergy between the two. The degradation rate of crystal violet was 91.19%. Graphical Abstract: